2020
DOI: 10.21608/ejhm.2020.120007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nicotine on the Rat’s Tongue and the Possible Protective Role of Royal Jelly Light and Scanning Electron Microscopic Study

Abstract: Background: nicotine (NIC) is an active substance in tobacco, the excessive use of tobacco products has been associated with various lesions in the oral cavity. Royal jelly (RJ) believed by many authors to be an anti-oxidant that protects different organs. Aim of the work: this study aimed to detect the effect of nicotine on the structure of the tongue and the possible protective effect of royal jelly. Materials and methods: 30 adult male rats were equally categorized into 3 groups. Group I: 10 rats used as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…To enhance oral mucosa wound healing in smokers, some researchers tried to decrease e-cigs harmful effects by using antioxidant materials such as vitamin C [9] , Royal jelly [10] and ginger [11] . Interestingly, It has been reported that ginger volatile oil possesses antioxidant and antiinflammatory properties [11] .…”
Section: Introductionmentioning
confidence: 99%
“…To enhance oral mucosa wound healing in smokers, some researchers tried to decrease e-cigs harmful effects by using antioxidant materials such as vitamin C [9] , Royal jelly [10] and ginger [11] . Interestingly, It has been reported that ginger volatile oil possesses antioxidant and antiinflammatory properties [11] .…”
Section: Introductionmentioning
confidence: 99%